2022
DOI: 10.1039/d1na00819f
|View full text |Cite
|
Sign up to set email alerts
|

High-performance and selective adsorption of ZIF-8/MIL-100 hybrids towards organic pollutants

Abstract: Environmental contamination by organic pollutants has become a pressing concern. In this study, metal-organic framework composites with a core-shell structure of MIL-100 wrapped around ZIF-8 (ZIF-MIL hybrids) were synthesized and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Tetracycline (TC) is commonly used for antibiotic adsorption studies on ZIF-8 [22]. However, this adsorbate played a pollutant role in contaminated water treatment in these works.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetracycline (TC) is commonly used for antibiotic adsorption studies on ZIF-8 [22]. However, this adsorbate played a pollutant role in contaminated water treatment in these works.…”
Section: Introductionmentioning
confidence: 99%
“…Valuably, the effect of pH value on release speed was examined and gave an important result in using ZIF-8 for drug delivery vehicles. In the following, some medicines loaded to ZIF-8 based on a variety mechanism: 6-mercaptopurine [19], doxorubicin [20], celecoxib [21], amoxicillin [22] or minocycline [23].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of industries, the sewage discharge is increasing gradually, and the water pollution problem is becoming more and more serious. − Some dyestuff and heavy metal ion sewage produced by some industries is difficult to degrade and dyestuff molecules , and heavy metal ions can exist in the natural environment for a long time. − The most important thing is that these dyestuffs and ions as carcinogens seriously affect the health of water organisms and human beings. Therefore, necessary treatment is needed before sewage is discharged. − With the development of society, the treatment of dyestuffs and heavy metal ions − in sewage has become the focus of developing modern civilized cities. − However, because the composition of dyestuffs and heavy metal ions is very complex, the degree of pigment is too high, and the influence of acid and alkali is great, it is very hard for sewage treatment at present.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The unique structure of ZIFs, with rich pore structure and high specific surface area and their resistance to chemical and thermal attack, 3 have led to their applications in various areas, such as air pollution control and adsorption. 4,5 Adsorption desulfurization (ADS) is considered a promising ultra-depth desulfurization technology to solve the inefficient use of fossil fuels and other serious environmental problems. Wu et al 6 found that ZIF-8 could remove thiophene by about 70%.…”
Section: Introductionmentioning
confidence: 99%